Hay orbakhnam ěnkerutéan Ayntápi orbanots ́Chiwnie-Libanan-Aknark me hastatutéan paraganerun ew kárameay patmutéan vray, 1919 Ōgostosē 1923 Hunis. - Hay orbakhnam ěnkerutʻiwn. (Tufts University. Tisch Library., 2019)
1 online resource (40 pages); Report.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2018. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.